Aquinas on creation and the metaphysical foundations of science - Carroll, William E. (Sapientia, 1999)
In John Milton's Paradise Lost, God sends the angel Raphael to Adam and Eve in the Garden of Eden to inform them of Satan's rebellion and of the fallen angel's consequent plan to seduce the happy couple. Raphael's story of the fall of Satan and the creation of the world is part of God's purpose to make sure that the first human beings are «sufficient to stand», although «free to fall». Indeed, the defense of freedom, divine and creaturely, is at the heart of Milton's great epic. Unlike those who deny human freedom in order to protect divine omni-potence, Milton seeks to affirm man's freedom in a world created by God.